Heartfelt Listening: Enhanching Student Empathy Through Peer Counseling Training - Tina Khostarina; Nur Aisyah Rahmani Nasution; Agnes Sandra; Rakel Abimael; Indra YI. Setiawan; Sharon Antonia Trifosa Lieando; Brigitta Juliana Situmorang; Tina Margareta (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Social and academic changes significantly impact the quality of students' daily social interactions. One of the key factors contributing to the decline in social interactions is a lack of empathy. A decline in empathy has become increasingly prevalent among university students, making it more difficult for them to understand and appreciate the emotions of others. This condition is reflected in the rising cases of bullying and can also affect students' academic success. The aim of this program is to enhance students' empathy through peer counseling training. The training method was implemented through education and role-playing activities to 16 psychology students. The effectiveness of the training was evaluated through pre-test and post-test questionnaires assessing empathy levels. The results showed a significant difference in empathy levels before and after the training. The increase in empathy was evidenced by the average pre-test score of 53.00 and the average post-test score of 62.00. The implications of this program suggest that peer counseling training can effectively enhance empathy among students. Empathy is a crucial quality for psychology students, enabling them to better understand, support, and assist their peers in navigating various challenges. Perubahan sosial dan akademik mempengaruhi kualitas interaksi sosial mahasiswa sehari-hari. Salah satu faktor penurunan interaksi sosial ini adalah kurangnya empati. Penurunan empati marak terjadi di kalangan mahasiwa. Hal ini membuat para mahasiswa menjadi kesulitan dalam memahami dan menghargai emosi orang lain. Kondisi ini dapat terlihat dari semakin tingginya kasus bullying dan juga dapat berpengaruh terhadap kesukesesan akademik. Tujuan dari kegiatan pengabdian masyarakat ini adalah untuk meningkatkan empati melalui pelatihan konseling sebaya. Metode pelatihan dilaksanakan melalui pemberian edukasi dan roleplay kepada 16 orang mahasiswa. Evaluasi terhadap hasil pelatihan dilakukan melalui kuesioner pre-test dan post-test terkait empati. Berdasarkan hasil pre-test dan post-test terhadap peserta pelatihan, diketahui bahwa terdapat perbedaan tingkat empati sebelum dan sesudah mengikuti pelatihan. Peningkatan empati yang siginifikan ditunjukkan dari skor rata-rata pre-test sebesar 53,06 dan rata-rata post-test sebesar 62,00. Implikasi dari pengabdian ini menunjukkan bahwa pelatihan konselor sebaya dapat meningkatkan empati pada mahasiswa. Empati menjadi kualitas penting bagi mahasiswa psikologi agar dapat memahami, mendukung, dan membantu teman sebaya dalam menghadapi tantangan yang dihadapi.